P-631 Embryo euploidy rates following follicular or luteal start ovarian stimulation. A prospective study with repeated ovarian stimulation ovarian stimulation cycles. (6th August 2021) - Martinez, F; Clua, E; Roca, M; Garcia, S; Parriego, M; Polyzos, N P
Abstract: Study question: Is there any difference in embryo euploidy rates following luteal phase phase (LS) and follicular phase (FS) start ovarian stimulation. Summary answer: The number of euploid blastocysts and embryo euploidy rate are comparable when comparing FS and LS. What is known already: Random start ovarian stimulation (starting at any time of the cycle) has been traditionally used in women undergoing urgent fertility preservation for medical reason. Although there is accumulating evidence that in infertile women, LS can result in equivalent number of oocytes and embryos as compared with FS, no study has evaluated the effect of luteal phase start ovarian stimulation on embryo euploidy rates. The current study is the first prospective study designed to evaluate embryo euploidy rates in donors undergoing two identical consecutive ovarian stimulation protocols within a period of 6 months starting either in the (FS), or (LS). Study design, size, duration: In a prospective study, conducted between May 2018 and January 2020, 40 oocyte donors underwent two consecutive ovarian stimulation protocols within a period of 6 months with an identical fixed GnRH antagonist protocol starting either in the early follicular (FS), or and luteal menstrual cycle phase (LS). Participants/materials, setting, methods: All participants underwent two identical consecutive ovarian stimulation cycles with 150μg corifollitropin alfa followed by 200 IU rFSH in a fixed GnRH antagonist protocol either in the FS or LS. Six MII oocytes from the same oocyte donor, from each stimulation cycle, were allocated to the recipients and were inseminated with the same sperm sample (recipients partner sperm or donor sperm). Embryos were cultivated to blastocyst stage followed by preimplantation genetic testing for aneuploidies (PGT-A). Main results and the role of chance: When comparing FP with LP, the duration of ovarian stimulation was significantly shorter (9.68± 2.09 vs 10.93± 1.55 days), 95% CI [-1.95; -0.55] and a higher total additional dose of daily recFSH was significantly lower (526.14± 338.94 IU vs 726.14± 366.27), 95% CI [-315, 12; -84, 88] when CPT was administered in the luteal phase. . There were no differences in the hormone values on the triggering day (Estradiol 2137.61±1198.25 pg/ml vs 2362.96±1472.89); 95% CI [-1160.45;709.76]. Overall no differences were observed in the number of oocytes (24.84± 11.200 vs 24.27± 9.08); 95% CI[-2, 61; 3.75] and MII oocytes (21.41±10.19 vs 21.59± 8.81), 95%CI [-2.72; 2.35] retrieved between FP and LP cycles in the oocytes donors. Following oocyte allocation and fertilization to the recipients, a total of 245 blastocysts were biopsied (blastocyst formation rate 245/408, 60.05%), 117 in FP group and 128 in LP group. The overall blastocyst euploidy rate was 59.18% . There were no differences in the number of euploid embryos between FS (1.59±1.32) and LS (1.70±1.29), mean difference 0.11, 95%CI [-0.65; 0.46]. Finally, there were no differences in the percentage of euploid embryos per oocytes inseminated between FS [70/287 (24.4%)] and LP [75/278 (24.7%), mean difference -0.027, 95%CI [-0.11; 0.06]. Limitations, reasons for caution: The study was performed in oocyte derived from potentially fertile young oocyte donors thus caution is needed when extrapolating the results in oocytes derived from infertile women of older age. Wider implications of the findings: Luteal phase stimulation does not alter embryo euploidy status as compared with follicular phase stimulation and thus it appears that it can be safely used not only in cases of urgent medical fertility preservation but also in patients undergoing ovarian stimulation for IVF/ICSI. Trial registration number: Clinical Trials Gov (NCT03555942).